Hubungan Pengetahuan terhadap Swamedikasi Penyakit Gastritis pada Mahasiswa Kesehatan dan Non Kesehatan: Literatur Review - Shalena Tasya Rahmawati; Ihsanti Dwi Rahayu (CV. ITTC INDONESIA, 2026)
Introduction: Self-medication is an effort applied to treat symptoms and complaints of mild signs of disease. Gastritis or better known as ulcers is one of the disorders of the digestive tract caused by inflammation of the gastric mucosa and submucosa, which can be triggered by irritation and infection factors. Methods: This literature review was conducted by searching journal databases, including ScienceDirect, PubMed, and Google Scholar with the keyword